Seasonal population fluctuation of Phytophthora nicotianae var. parasitica in Kinnow mandarin orchards under Punjab conditions - S.K. THIND, UMESH KUMAR DHAKAD*, SARBJEET KAUR and (Indian Phytopathology, 2016)
Phytophthora diseases of Kinnow mandarin create serious threat in production and are responsible for ruin and decline of orchards in Punjab.The prevalence of Phytophthora diseases in the districts of Fazilka (10-100%), Bathinda (10-50%) and Hoshiarpur (10-50 %) has been reported.The population dynamics of pathogen under Punjab conditions were determined. Soil samples were collected along feeder roots from the Kinnow mandarin orchards at three locations viz.Abohar, Hoshiarpur and Ludhiana. Soil plating method was adopted by using selective media (PARPH-CMA). Significantly higher pathogen population (342, 402 and 354 propagules/cc of soil) was recorded in the month of July in Abohar, Hoshiarpur and Ludhiana respectively as compared to other months. Similarly, lowest population (7, 8 and 8 propagules/cc of soil) was recorded in June. Pathogen population showed the positive correlation with mean temperature, rainfall and relative humidity.